(untitled) (AYUSHDHARA, 2016)
Haridra is a potent medicinal herb used traditionally since ancient times for the treatment of various skin disorders, liver disorders and respiratory disorders and are well documented in Ayurvedic literatures. This is again revalidated by recent researches done on the biological and pharmacological actions like anti-inflammatory, antioxidant, anti diabetic, antibacterial, hepatoprotective, expectorant, anti cancerous, anti mutagenic, anti melanogenic, free radical scavenging properties of phytoconstituents of Curcuma longa like curcumin, curcuminoids etc. Due to high potency and therapeutic value of drug its demand is increasing in pharmaceutical industries for preparation of various formulations containing Curcuma longa or its constituents. Cultivation of drug on large scale is done for trading as India is one of the main trading center of Curcuma longa (Indian Saffron) and its various varieties are available in market. This review focuses on these potent pharmacological properties with macroscopic and microscopic features of both cured and uncured available rhizomes of Haridra in market with nutritional value and its wide range of use in cosmeceutical and nutraceutical industry which proves it as arising magical herb in pharmaceutical industry for preparation of formulations used in various diseases.